Egg's vitamin E deposition of Kedu breeder chicken fed improved diets - Wahyuni, H.I.; Suthama, N.; Mangisah, I.; Krismiyanto, L. (Diponegoro University, 2018)
The research aimed to evaluate dietary vitamin E deposited into the egg of Kedu breeder hen reared in situ and fed an improved diet supplemented with vitamin E. A total of 75 breeder hens and 15 cockerel of Kedu chicken aged ± 12 months, with average body weight of 1667 ± 237 and 2295 ± 250 g/bird, respectively, were distributed into 15 units of semi intensive housing system. A completely randomized designed (CRD) was arranged in the present research with 3 dietary treatments, namely farmer formulated ration (T0), improved ration (T1), and T1 + 6.28 mg/kg vitamin E (T2). Parameters observed were feed consumption, consumption and retention of vitamin E, egg’s vitamin E, egg’s vitamin E deposition efficiency, hen day production (HDP) and egg weight. All data gathered were subjected to analysis of variance and Duncan’s multiple range test to differentiate between treatments. Variables, except feed consumption, HDP and egg weight, were significantly (P<0.05) influenced by dietary treatment. Vitamin E consumption and retention, and deposition increased due to feeding effect of improved diet and supplementation of vitamin E. Dietary vitamin E of farmer’s ration deposited into the egg indicated the highest value (229.23%) followed by improved ration (51.85%), and improved ration + vitamin E was the lowest (5.38%). In conclusion, Kedu hen is likely have a limitation on vitamin E deposited into the egg when the improved ration supplemented with vitamin E is fed, and vitamin E supplementation should be implemented together with the increase of fat content in the ration.